Is there a correlation between a 20-min pad-test and subjective urine leakage amount? - Prudencio, Caroline Baldini [UNESP]; de Azevedo Ferreira, Letícia; Gimenez, Márcia Maria; de Aquino Nava, Guilherme Thomaz [UNESP]; Bortolini, Maria Augusta Tezelli; Castro, Rodrigo Aquino; Fitz, Fátima Faní (Springer Nature, 2021)
Introduction and hypothesis: The quantification of urinary incontinence (UI) is widely used in clinical practice to guide the prognosis and treatment, and the pad test is an inexpensive, quick, and easy tool to assess UI that has been used in studies in the literature. Another way to evaluate UI is the subjective urine leakage amount, but no studies have tried to correlate it with the 20-min pad test. Therefore, this study aimed to assess the correlation of the 20-min pad test with the subjective urine leakage amount and compare it with the pelvic floor function. Methods: This is a cross-sectional study with a sample size of 72 participants. It evaluated pelvic floor muscle strength as well as the duration of symptoms and pad weight. It used mean, standard deviation, median, and 95% confidence interval. In addition, ANOVA, Kruskal-Wallis, and Spearman’s correlation coefficient were used. The significance level was fixed at 5% (significant if P < 0.05). Results: Only age was different between leakage volumes; participants who report greater UI volume were older than the participants who leaked less urine. There were no differences related to the duration of symptoms between different UI volumes and pad weights according to the subjective volume reported. Spearman’s coefficient between pad weight and subjective volume of urine leakage was rs = 0.558 (P ≤ 0.0001), demonstrating a moderate positive correlation. Conclusions: There was a moderate correlation between the UI volume reported and the 20-min pad test. Additionally, no differences related to pelvic floor function were detected.
Keywords: Female; Incontinence pads; Subjective; Urinary incontinence